2017
DOI: 10.1049/trit.2017.0017
|View full text |Cite
|
Sign up to set email alerts
|

Mixed reality system for industrial environment: an evaluation study

Abstract: Enabling technologies for augmented reality (AR)/mixed reality have been improved and refined throughout the last years and more recently they seem to have finally passed the demo stage to become ready for practical industrial and commercial applications. But what are the measurable advantages in using them? This study tries to answer this question by presenting the results of a comprehensive evaluation study conducted in a real industrial environment on the widest number of real users involved in such kind of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…• Several AR applications offer two distinct modes: editing (to link digital information with physical objects) and exploring (to locate the POIs) [1,6]. While the editing mode requires in-situ positioning of POIs and therefore the need for pointing at any position on screen, the exploring mode, as in the two uses cases above, involves selecting POIs.…”
Section: Poi Expansion: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…• Several AR applications offer two distinct modes: editing (to link digital information with physical objects) and exploring (to locate the POIs) [1,6]. While the editing mode requires in-situ positioning of POIs and therefore the need for pointing at any position on screen, the exploring mode, as in the two uses cases above, involves selecting POIs.…”
Section: Poi Expansion: Designmentioning
confidence: 99%
“…(2) Relative touch pointing: Fix the cursor in the physical world (Relative Pointing technique [24]), and control it with left thumb strokes on screen (Figure 5f2), namely Voronoi Jumping-Relative technique. When coupling these two techniques with the POI expansion technique, users are able to (1) select/open a POI without aligning the cursor with the POI, (2) place the cursor into the menu without additional movement, and (3) perform either a Physical or Relative pointing to select an item in the menu.…”
Section: Implemented Jumping Cursor Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ulery and Hyman [8] proposed a modified determination method (MDM) based on the measurement of various gas pressures, then the ideal gas law is used to calculate the desorption of gases under standard temperature and pressure conditions (STP). Mavor et al [9,10] established a process for the estimation of gas content based on the USBM direct assay. Saghafi et al [11] showed that the initial desorption of coal gas has an exponential relation with time.…”
Section: Introductionmentioning
confidence: 99%